THE INFLUENCE OF THE TOOTH BANK AT THE PETROLINA HEALTH COLLEGE IN PERNAMBUCO: AN EXPERIENCE REPORT - Caroline Ribeiro Lacerda, Anne; Cirqueira Araujo Telles Nouzinho, Clarisse; Sanchez da Cunha, Fernanda; Amariz Silva, Giovana; Cavalcante Carneiro, Laís; Jordania Lino Figueredo, Lívia; de Souza Pereira, Malvina; da Silva Oliveira, Thaís (Health and Society, 2025)
Introduction: The Human Teeth Bank institution plays an important role in understanding teeth as organs and in controlling the illegal trade of teeth in Dentistry schools. Considering that the loan of teeth is essential in the training of professionals and future dentists, this is an academic extension project of Faculdade Soberana, which aims to regulate, monitor, and ensure the loan of natural teeth to students and professors. Objectives: This work aims to analyze, through this study, the performance of the Human Teeth Bank of Vale do São Francisco and how it is given regarding the legality of the origin of the teeth correlated with the receipt, preparation, and distribution. Materials and methods: An experience report was made of the activities carried out by the project participants since its foundation in March 2022 to December 2023, in addition to a systematization of the work, discussing the processes and management based on literature. Results: It was possible to analyze that the extension project plays an important role in the relationship of integration between students, professors, and technicians in the activities developed. As a consequence, it assumes notoriety in the ethical and bioethical sphere by eliminating the illegal form of tooth trade and contributing to distribution in addition to meeting educational and clinical needs. Conclusion: It is essential that during the training of dentists, there is the dissemination of content about the functioning and ethical and legal requirements for the use of human teeth, thus being able to eliminate the illegal trade of organs and contribute to enriching academic studies and research.